2016
DOI: 10.1117/1.jbo.21.9.098002
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy with helium–neon laser improved viability of osteoporotic bone marrow-derived mesenchymal stem cells from ovariectomy-induced osteoporotic rats

Abstract: The purpose of this study was to evaluate the influences of helium–neon (He–Ne) and infrared (IR) lasers on the viability and proliferation rate of healthy and ovariectomy-induced osteoporotic (OVX) bone marrow mesenchymal stem cells (BMMSCs) in vitro. MSCs harvested from the BM of healthy and OVX rats were culture expanded. He–Ne and IR lasers were applied three times at energy densities of 0.6, 1.2, and 2.4??J/cm2 for BMMSCs. BMMSCs viability and proliferation rate were evaluated by MTT assay on days 2, 4, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…The osteogenic induction medium culture medium was replaced by fresh medium immediately before irradiation. The LLLT protocol (He‐Ne laser, 632.8 nm, 3 mW, 1.2 J/cm 2 , 378 s, 1.56 cm laser beam diameter, 1.96 cm 2 laser beam surface area, and 0.0016 W/cm 2 ) was the same as in our previous study . The He‐Ne laser beam was expanded and collimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The osteogenic induction medium culture medium was replaced by fresh medium immediately before irradiation. The LLLT protocol (He‐Ne laser, 632.8 nm, 3 mW, 1.2 J/cm 2 , 378 s, 1.56 cm laser beam diameter, 1.96 cm 2 laser beam surface area, and 0.0016 W/cm 2 ) was the same as in our previous study . The He‐Ne laser beam was expanded and collimated.…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance of the formazan solution from the wells was calculated on an ELISA reader at a wavelength of 570 nm using microtiter plate reader (Anthos 2020 Microplate Readers, Biochrom Ltd., Cambridge, UK) and optical densities (OD) were reported. A 620 nm filter was used for background reading …”
Section: Methodsmentioning
confidence: 99%
“…It was shown that a low-level laser in the osteoporosis MSCs from ovariectomized mice could significantly increase the optical density and cell viability compared to the control group. 39,40 Also, another study showed that the effects of a low-power laser strongly depended on wavelength parameters, the number of laser therapy sessions, the state of MSC physiology, and the type of the laser. 40 In Europe, about 1.5 million patients undergo jaw repair every year.…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…39,40 Also, another study showed that the effects of a low-power laser strongly depended on wavelength parameters, the number of laser therapy sessions, the state of MSC physiology, and the type of the laser. 40 In Europe, about 1.5 million patients undergo jaw repair every year. Despite surgical interventions, about 20% of them still have dysfunction.…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…5 Wound healing is a complicated process that involves clot formation, inflammation, granulation, epithelialization, and remodeling. 7,8 Studies on wound healing have investigated the effect of oxygen therapy, [9][10][11] biomechanics, 12 radiotherapy and medical pomades. 13 Low-level laser therapy (LLLT) is a good modality for wound healing.…”
Section: Introductionmentioning
confidence: 99%